Biocompatibility, hemostatic properties, and wound healing evaluation of tilapia skin collagen sponges. (January 2021) - Wang, Tong; Yang, Lintong; Wang, Guangfei; Han, Lei; Chen, Kaili; Liu, Ping; Xu, Shumin; Li, Dongsheng; Xie, Zeping; Mo, Xiumei; Wang, Lei; Liang, Haiyue; et al.
Dialyzed tilapia skin collagen sponge (DTSCS) and self-assembled tilapia skin collagen sponge (STSCS) were prepared by freeze-drying. The raw components used in the fabrication of DTSCS and STSCS were separated and purified from tilapia fish skin. It is anticipated that these collagen sponges could be developed into medical dressings for hemostasis and wound healing. The aim of the present research was to explore the possibility of DTSCS and STSCS as medical dressings and compare their differences by scanning electron microscopy (SEM), water absorption measurement, differential scanning calorimetry (DSC), measurement of porosity, cytotoxicity, hemolysis, in vivo biocompatibility, and evaluation of hemostatic performance and wound healing. The results indicate that DTSCS and STSCS are suitable materials for use in medical applications with a loose and porous structure, high water absorption, high porosity, and high thermal stability. The materials also displayed good biocompatibility, including excellent blood compatibility, a lack of cytotoxicity, with no apparent rejection following implantation. STSCS exhibited rapid hemostasis and promoted healing, with slightly greater efficacy than DTSCS. The hemostatic properties and promotion of healing in DTSCS was similar to that of commercial bovine collagen sponge. Therefore, DTSCS and STSCS both represented excellent potential candidate materials for use as hemostatic agents and wound dressings.